Sustainable economic growth and exhaustible resources: A model and estimation for the US. Issue 2 (2002) - Scholl, Almuth; Semmler, Willi
Abstract : This paper studies current models on sustainable economic growth with resource constraints and explores to what extent resource constraints can be overcome by substitution and technological change. We also study the problem of intergenerational equity and the different criteria that have been suggested in the literature. The central part of this paper is the presentation of stylized facts on exhaustible resources and an estimation of a basic model with resource constraints for US time series data. The estimated years left until depletion and the empirical trends of the ratios of capital stock and consumption to resources seem to indicate that there might be a threat to sustainable growth in the future. In our estimation, we obtain parameter values, which help to interpret the extent to which growth with exhaustible resources is sustainable.